2012
DOI: 10.1111/j.1464-5491.2012.03757.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity level and body composition among adults with Type 1 diabetes

Abstract: As in the population without diabetes, an active lifestyle is associated with a better body composition profile in adults with Type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 26 publications
(32 reference statements)
0
36
2
Order By: Relevance
“…The rate of severe hypoglycemia with coma was lowest in the most active subjects, irrespective of age or sex. Regarding findings from other studies, the effect of PA on the occurrence of hypoglycemia is still controversial, as some studies have shown more hypoglycemic events in physically active subjects with type 1 diabetes (30,31), whereas others have failed to find this relationship (12,32). Moreover, there is a lack of sex-or age-specific analyses.…”
Section: Discussionmentioning
confidence: 96%
“…The rate of severe hypoglycemia with coma was lowest in the most active subjects, irrespective of age or sex. Regarding findings from other studies, the effect of PA on the occurrence of hypoglycemia is still controversial, as some studies have shown more hypoglycemic events in physically active subjects with type 1 diabetes (30,31), whereas others have failed to find this relationship (12,32). Moreover, there is a lack of sex-or age-specific analyses.…”
Section: Discussionmentioning
confidence: 96%
“…1,2 Despite these benefits, most adults with T1D participate less frequently in PA than their nondiabetic counterparts 3 and may adopt unhealthy lifestyles that contribute to cardiometabolic risk. 4 Although the reasons for this are multifactorial, including concerns over loss of control and low fitness levels, the overriding barrier to PA appears to be fear of severe hypoglycemia, coupled with a lack of knowledge of effective strategies for hypoglycemia avoidance.…”
Section: Original Articlementioning
confidence: 99%
“…An isoprime stable isotope ratio mass spectrometer connected to a Multiflow-Bio module for Isoprime and a Gilson 222XL Autosampler (GV Instruments, Manchester, UK) were used for daily energy expenditure measurements. 47 The stability tests performed each day before testing gave an SD of 0.026% for deuterium and 0.004% for 18 O.…”
Section: Physical Activity Levelmentioning
confidence: 98%